Savoirs traditionnels et connaissances scientifiques pour une réduction de la vulnérabilité de l’habitat rural face aux aléas naturels en Haïti - Annalisa Caimi; Florent Vieux-Champagne; Philippe Garnier; Hubert Guillaud; Olivier Moles; Laurent Daudeville; Yannick Sieffert; Stéphane Grange (Field Actions Science Reports, 2013)
Following the earthquake that struck Haiti in 2010, observations have demonstrated the relevance of certain traditional building techniques that succeeded in limiting the occupants’ exposure to the risk of severe injury. Identifying and understanding the specificities of existing building structures and know-how provides a starting-point for improving building methods and reinforcing skills in order to reduce the long-term vulnerability of local communities. This paper presents two research works that address, from complementary angles, the issues of building in a risk-prone environment. The first, from the field of architecture, outlines a participatory methodology for analyzing local building practices with a view to developing them and making technical improvements. The second, from an engineering perspective, focuses on an experimental computer-aided scientific study of a building system used for post-earthquake reconstruction.